2016
DOI: 10.1039/c5ta09546h
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Sb2S3nanocrystals: synthesis, characterization and fabrication of solid-state semiconductor sensitized solar cells

Abstract: Antimony sulfide nanocrystals of various shapes and different phases are synthesized using a colloidal hot-injection method, and the as-prepared nanocrystals are used as a light harvesting material in photovoltaic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…95 A device with a ZnO-nw/TiO 2 /Sb 2 S 3 / P3HT/Au structure demonstrated 2.3% PCE and V OC of 656 mV under optimized conditions. There were more attempts to modify SSC fabrication stages, such as to use Sb 2 S 3 quantum dots, [96][97][98] pre-formed HTL, 99 and alternative electron transport materials, 100,101 but their performance was significantly lower than that of the SSC device with conventional architecture.…”
Section: Semiconductor-sensitized Solar Cellsmentioning
confidence: 99%
“…95 A device with a ZnO-nw/TiO 2 /Sb 2 S 3 / P3HT/Au structure demonstrated 2.3% PCE and V OC of 656 mV under optimized conditions. There were more attempts to modify SSC fabrication stages, such as to use Sb 2 S 3 quantum dots, [96][97][98] pre-formed HTL, 99 and alternative electron transport materials, 100,101 but their performance was significantly lower than that of the SSC device with conventional architecture.…”
Section: Semiconductor-sensitized Solar Cellsmentioning
confidence: 99%
“…The properties of antimony chalcogenides are determined predominantly by their components, crystal structures, sizes, and morphologies . Therefore, the synthesis of antimony chalcogenide materials with well‐controlled components, sizes, and shapes is of great significance for their application.…”
Section: Materials Fabrication Approachesmentioning
confidence: 99%
“…Metal‐organic precursor solutions can be prepared by dissolving metal oxides, metal hydroxides, metal chlorides, metal acetates, and metal acetylacetonates in thioglycolic acid and ethanolamine . Abulikemu et al reported a hot‐injection method to fabricate Sb 2 S 3 nanocrystals using antimony chloride as a source of Sb, bis(trimethylsilyl) sulfide as a source of S and oleic acid and 1‐octadecene as solvents. The nanocrystals obtained can be redispersed in toluene for spin‐casting deposition of Sb 2 S 3 films.…”
Section: Materials Fabrication Approachesmentioning
confidence: 99%
“…19,20 These contrasts in the molar ratios of Bi/(Sb+Bi) have been ascribed to the operation of so-called semi-metal boiling, during which a sudden alteration in the Sb 2 S 3 /Bi 2 S 3 (Sb/Bi) ratio arises at a specific point along the flow path due to preferential volatilisation and loss of antimony from the ore fluid. [20][21][22] Numerous approaches have been employed for the preparation of Sb 2 S 3 and Bi 2 S 3 nanoparticles and thin films including solvothermal, 23,24 hydrothermal, 25,26 single-source routes, [27][28][29][30] colloidal methods; 16,31,32 melt thermolysis, 33 dip-dry techniques, 34 chemical bath deposition, 35,36 aerosol-assisted chemical vapour deposition (AA-CVD), 37 spray pyrolysis, 38,39 and successive ionic layer adsorption reactions (SILAR) have also been used. 40,41 Solventless thermolysis has advantages over other routes, as it is a simple method in which solid state decomposition of a precursor is achieved by thermal treatment under inert conditions.…”
Section: Introductionmentioning
confidence: 99%